Pengaruh pemasaran syariah berkonsep soul share, kepuasan, keunggulan produk terhadap loyalitas nasabah: Studi kasus pada BMT UGT Nusantara Gadang - Azam, Rifki Muhamad (Maliki Interdisciplinary Journal, 2024)
The purpose of this research is to determine the effect of sharia marketing with the concept of soul share, satisfaction, product excellence on customer loyalty of BMT UGT Nusantara Gadang. This type of research is quantitative research. The type of data used is primary data obtained through distributing questionnaires to customers. The conclusion of this study is that the variable that has the most influence on customer loyalty is the sharia marketing variable with the concept of soul share (x1), while the product excellence (x2) variable has no effect on customer loyalty of BMT UGT Nusantara Gadang.